Chemical and Cyclic Degradation of Geosynthetic-Soil Interface - Kwak, C.W.; Park, I.J.; Park, J.B. (Asian Journal of Chemistry, 2014)
Different materials comprise interface at each boundary and the interface exists inevitably in all geotechnical systems. The interface shows complicated and sensitive behaviour because it is affected by many practical factors such as material, load and environment. Geosynthetic-soil interface is typical at the waste landfill site and the dynamic shear behaviour is critical to the seismic stability of the site. Chemical aggressor in the leachate affects the shear strength of the geosynthetic-soil interface. In this research, chemical degradation of the interface was investigated by cyclic simple shear test and different shear stress degradation patterns were estimated. The disturbed state concept was employed to analyze the test results and new disturbance function parameters with respect to the different damage patterns were suggested. Microscopic observation by focused ion beam was introduced and utilized to clarify the variation of interface damage. Consequently, the variation of the cyclic shear behaviour at geosynthetic-soil interface was due to the different damage pattern at soil particle surface based the focused ion beam results.